Human capital gaps in vaccine development: an issue for global vaccine development and global health. Issue 1 (23rd February 2017) - Cawein, Andrea; Emini, Emilio; Watson, Michael; Dailey, Joanna; Donnelly, John; Tresnan, Dina; Evans, Tom; Plotkin, Stanley; Gruber, William
Abstract : Despite the success of vaccines in reducing the morbidity and mortality associated with infectious diseases, many infectious diseases, both newly emerging and well known, lack vaccines. The global capability for beginning‐to‐end vaccine development has become limited, primarily owing to a scarcity of human capital necessary to guide the development of novel vaccines from the laboratory to the marketplace. Here, we identify and discuss the gaps in human capital necessary for robust vaccine development and make recommendations to begin to address these deficiencies.